Caregiver burden and health-related quality of life: A study of informal caregivers of older adults in Ghana - Williams Agyemang-Duah; Alhassan Abdullah; Mark W. Rosenberg (BMC, 2024)
Abstract Background Similar to many developing countries, caregiver burden remains high in Ghana which may affect informal caregivers of older adults' health-related quality of life (HRQoL). However, no study has examined the association between caregiver burden and HRQoL among informal caregivers of older adults in Ghana to date. Understanding this association may well help to inform health and social policy measures to improve HRQoL among  informal caregivers of older adults in Ghana. Situated within a conceptual model of HRQoL, the purpose of this study was to examine the relationship  between caregiver burden and HRQoL among informal caregivers of older adults in Ghana. Methods We obtained cross-sectional data from informal caregiving, health, and healthcare (N = 1853) survey conducted between July and September 2022 among caregivers (≥ 18 years) of older adults (≥ 50 years) in the Ashanti Region of Ghana. The World Health Organization Impact of Caregiving Scale was used to measure caregiver burden. An 8-item short form Health Survey scale developed by the RAND Corporation and the Medical Outcomes Study was used to measure HRQoL. Generalized Linear Models were employed to estimate the association between caregiver burden and HRQoL. Beta values and standard errors were reported with a significance level of  0.05 or less. Results The mean age of the informal caregivers was 39.15 years and that of the care recipients was 75.08 years. In our final model, the results showed that caregiver burden was negatively associated with HRQoL (β = − .286, SE = .0123, p value = 0.001). In line with the conceptual model of HRQoL, we also found that socio-economic, cultural, demographic and healthcare factors were significantly associated with HRQoL. For instance, participants with no formal education (β = −1.204, SE= .4085, p value = 0.01), those with primary level of education (β = −2.390, SE= .5099, p value = 0.001) or junior high school education (β = −1.113, SE= .3903, p value= 0.01) had a significantly decreased HRQoL compared to those with tertiary level of education. Participants who were between the ages of 18-24 (β = 2.960, SE= .6306, p value=0.001), 25-34 (β = 1.728, SE= .5794, p value = 0.01) or 35-44 (β = 1.604, SE= .5764, p value= 0.01) years significantly had increased HRQoL compared to those who were 65 years or above. Also, participants who did not utilize healthcare services in the past year before the survey significantly had increased HRQoL compared to those who utilized healthcare services five or more times in the past year (β = 4.786, SE=. 4610, p value= 0.001). Conclusion Consistent with our hypothesis, this study reported a significant negative association between caregiver burden and HRQoL. Our findings partially  support the conceptual model of HRQoL used in this study. We recommend that health and social policy measures to improve HRQoL among  informal caregivers of older adults should consider caregiver burden as well as other significant socio-economic, cultural, demographic, and healthcare factors.